Some physicochemical characteristics of cotton and citrus Greek honeys - BACANDRILSOS (Ν. ΜΠΑΚΑΝΔΡΙΤΣΟΣ) N.; PAPADOPOULOU (Π. ΠΑΠΑΔΟΠΟΥΛΟΥ) P.; VAVOULIDOU (Ε. ΒΑΒΟΥΛΙΔΟΥ) F.; TSIROYIANNIS (Β. ΤΣΙΡΟΓΙΑΝΝΗΣ) V. (Journal of the Hellenic Veterinary Medical Society, 2018)
Water content, pH, acidity, reducing sugars, apparent sucrose, hydroxymethyfurfural (HMF) content and diastase activity of cotton and orange honeys from different places of Greece have been measured. Samples in all the measured characteristics have been found to comply with the limits given by the E.U. Directive 74/409. These values were in agreement with those reported by other Greek researchers. Statistical analysis of the sample means of the physicochemical data showed that the two types of honey differ statistically in all the characteristics except that of apparent sucrose in which no significance was observed in the 0.05 level.